Study of Potential Use of Iron Mining Tailings Calcined in a Flash Furnace as Pozzolanic Material - Evandro Moraes da Gama; Paulo Roberto Gomes Brandão; Talita Caroline Miranda; Tamiris Seerig; Scott Ferson (Current Innovations in Chemical and Materials Sciences Vol. 2, 2023)
The main objective of this chapter is to show that fine mining tailings generated from iron mining have properties similar to kaolin, and clays rich in kaolinite, which are raw materials that when submitted to flash calcination result in prod- ucts with pozzolanic characteristics of excellent quality, and can be used to subs- titute Portland cement, mortar for iron ore tailings, cold pelleting of dam tail- ings, and as flexible pavements for the base and subbase of roads. The research involved characterizing the tailings both before and after calcination, and performing analysis on their chemical, mineralogical, thermogra- vimetric, and mechanical strength. Similarities between the results and those for regularly used pozzolans and metakaolin were found. The study of the morphology of the particles before and after calcination was conducted through analyses of images obtained by scan- ning electronic microscope. The pozzolanic activity of the fine mining tailings calcined with flash technology was evaluated in uniaxial compression trials, which show the excellent results.